Rules and regulators - Black, Julia (Clarendon Press, 1997)
Julia Black's book is the first authoritative study of rulemaking in one of the most important areas of economic life: financial services. The book has three main aims: first, to build on an analysis of the nature of rules and interpretation, drawing out the implications of this analysis to develop quality proposals for how rules could be used as instruments of regulation. Second, it links that analysis and set of proposals with an empirical study of the formation and use of rules in a particular regulatory system: financial services, and third, it evaluates the nature of the rulemaking process. The author's main case study, examining the use of 'self-regulation' in the financial services sector, complements the detailed analysis of rule formation and uses. The book will be an invaluable addition to the libraries of all public lawyers and all those with an interest in the provision and regulation of financial services.
Keywords: Asesores de inversiones - Estatus legal, leyes, etc - Gran Bretaña; Conseillers financiers - Statut juridique - Grande-Bretagne; Droit administratif - Philosophie; Procédure administrative - Philosophie; Regelgeving; Règlements (Droit administratif) - Philosophie; Règlements (Droit administratif) - Rédaction - Philosophie; Règlements (droit administratif) - Philosophie; Services financiers - Droit - Grande-Bretagne; Philosophie; Recht; Administrative law -- Philosophy; Administrative regulation drafting -- Philosophy; Delegated legislation -- Philosophy; Financial services industry -- Law and legislation -- Great Britain; Rechtsetzung; Finanzdienstleistung; Großbritannien